2013
DOI: 10.1208/s12249-013-0023-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Inclusion Complex of Curcumin–β-Cyclodextrin Nanoparticle to Enhance Curcumin Skin Permeability from Hydrophilic Matrix Gel

Abstract: Abstract. Curcumin (CUR) has various pharmacological effects, but its extensive first-pass metabolism and short elimination half-life limit its bioavailability. Therefore, transdermal application has become a potential alternative to delivery CUR. To increase CUR solubility for the development of a transparent homogenous gel and also enhance the permeation rate of CUR into the skin, β-cyclodextrin-curcumin nanoparticle complex (BCD-CUR-N) was developed. CUR encapsulation efficiency was increased by raising the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(115 citation statements)
references
References 20 publications
9
105
1
Order By: Relevance
“…In our previous study, a similar drug release study was conducted for pure curcumin powder. The results showed that less than 15% of curcumin was released within 1 h. 39) By contrast, in this study, curcumin was completely released from the fiber within 1 h.…”
Section: Fig 7 Thermal Properties Of Materials In the Fibercontrasting
confidence: 80%
“…In our previous study, a similar drug release study was conducted for pure curcumin powder. The results showed that less than 15% of curcumin was released within 1 h. 39) By contrast, in this study, curcumin was completely released from the fiber within 1 h.…”
Section: Fig 7 Thermal Properties Of Materials In the Fibercontrasting
confidence: 80%
“…Dia. : 21.5 mm) [29,30]. The drug is loaded films were suspended in glass vessels containing 50 ml of 0.1 M phosphate buffer saline (PBS; pH: 1.2., 4.5 and 7.4).…”
Section: Anti-oxidant Analysismentioning
confidence: 99%
“…The drug is loaded films were suspended in glass vessels containing 50 ml of 0.1 M phosphate buffer saline (PBS; pH: 1.2., 4.5 and 7.4). At appropriate time intervals (10,20,30,40, 60, 120 min) aliquots of solutions were withdrawn and the amount of curcumin released were evaluated by UV spectrophotometer at 424 nm [31]. The release was quantified by the following equation:…”
Section: Anti-oxidant Analysismentioning
confidence: 99%
“…Short-term clinical runs (6) demonstrated very low toxicity in a single daily doses of 12 and 8 g for 3 months. However, curcumin low solubility in aqueous solutions (7,8), instability in alkaline pH and short half-life lead to low oral bioavailability and therapeutic limitations (8)(9)(10)(11)(12)(13)(14)(15)(16). Curcumin solubility is a determining factor for its bioavailability when administered orally (17) and huge scientific work has been devoted to overcome this limitation (8,(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%